2022
DOI: 10.21831/progcouns.v3i1.48386
|View full text |Cite
|
Sign up to set email alerts
|

A review on family caregiving challenges in Malaysia

Abstract: Family caregiving often involves family members, relatives, and partners with whom the patients have a personal relationship to assist the care. The roles of caregivers are extensive and require a lot of effort, time, and commitment. These demands might possibly affect the life of caregivers. This paper aims to identify how family caregiving in Malaysia might have jeopardized the caregiver's life. A systematic approach analysis was utilized in this study while including seventeen articles. The exclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…These ndings matched with study by (Chan et al, 2022) entitled "A review on family caregiving challenges in Malaysia" and concluded that there is statistically signi cance difference pre and post intervention between levels of knowledge, burden of care, coping ways and quality of life among the family caregivers pre and post intervention at P<0.05*.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These ndings matched with study by (Chan et al, 2022) entitled "A review on family caregiving challenges in Malaysia" and concluded that there is statistically signi cance difference pre and post intervention between levels of knowledge, burden of care, coping ways and quality of life among the family caregivers pre and post intervention at P<0.05*.…”
Section: Discussionsupporting
confidence: 71%
“…Table (12): Illustrates the correlation between levels of knowledge, burden of care, coping ways, and quality of life of the studied family care providers throughout periods of intervention.…”
Section: Figure (2)mentioning
confidence: 99%
“…An interesting finding was that experiencing epistaxis was more common among Saudi nationals than non-Saudis, possibly linked to the prevalence of cultural and traditional home remedies for epistaxis in the native population. Widows also reported greater experience with epistaxis, likely due to being more actively involved in family caregiving roles after losing a spouse [ 21 ]. These findings provide vital insights into the demographic segments that should be targeted to improve awareness about first aid for epistaxis, such as youth and socially isolated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst other studies, studies [ 7 , 8 , 9 , 10 , 11 ] show that most literature on caregivers of people living with epilepsy tends to focus more on the epilepsy burden, primarily on children/teenagers living with epilepsy. On the other hand, [ 12 ] conducted a first-aid intervention study in the UK, and on many occasions, we found that initiatives such as these are specific to developed countries.…”
Section: Introductionmentioning
confidence: 99%